RAGI HEALTH MIX FOR MANAGING POLYCYSTIC OVARIAN SYNDROME - FORMULATION AND NUTRIENT ANALYSIS - T. T. JOLLY; A. THIRUMANI DEVI (The Journal of Research ANGRAU, 2023)
Polycystic Ovarian Syndrome, the most common endocrine disorder affecting women of reproductive age, affects between 5–10% of women globally. All PCOS-affected women should engage in lifestyle interventions including diet and exercise since losing weight decreases PCOS symptoms. Because of their greater concentrations of phenolic compounds, fibre, flavonoids, and phytosterols, millets outperform other cereals in terms of nutrition, health advantages, and phytochemical makeup.This study was conducted in May 2023. In this study, aim was to develop and assess a ragi-based nutritional supplement, high in micronutrients and fibre, for women with PCOS. The supplement was prepared in clean, and sanitary conditions. A panel of 30 judges conducted the organoleptic tests. Standard techniques were used to evaluate microbial activity and nutrient content.The prepared health mix was statistically significant (P< 0.05). After five days, the microbiological tests revealed that it was microbe-free. The health mix was shown to be abundant in fibre and micronutrients after a nutritional analysis. The results showed that the ragi supplement may be used to manage PCOS